Traumatic stress symptoms, mental splitting and burnout in health care professionals: a cross-sectional study - Riethof, Norbert; Bob, Petr (Frontiers in Psychiatry, 2024)
Background: Burnout syndrome usually begins with feelings of enthusiasm and idealized visualizations, and it is in contrast with subsequent disillusionment, disappointment, and symptoms which are related to chronic stress experienced later. This tendency to idealization is a parallel to the concept of "mental splitting" described by Kernberg with a pronounced "black and white" perceptual dichotomy between the early idealization and later disillusionment. This study intends examination of relationships between burnout syndrome, traumatic stress and Kernberg's concept of splitting. Methods and participants: In this study we have assessed 90 health care professionals (50 women and 40 men) working with a population of diabetic patients utilizing Burnout Measure (BM), Splitting index (SI) and Traumatic Stress Checklist -40 (TSC-40).Results: Study results indicate significant Spearman correlations between burnout syndrome (BM) and traumatic stress (TSC-40) in population of men (R=0.75, p<0.01) and of women (R=0.61, p<0.01), as well as between burnout syndrome (BM) and splitting (SI) for both genders: men (R=0.40, p<0.01), women (R=0.51, p<0.01). These findings may have implications for prevention and treatment of burnout syndrome.The current study findings provide implications that the defensive mechanisms of splitting and traumatic stress may allow for the prediction of burnout symptoms. This relation may potentially be of use in both the potential detection and prevention of burnout syndrome.